Implementation Of Character Education In The Student Council - Meitriana Mezi; Jagad Aditya Dewantara (Jurnal Basicedu, 2020)
This study aims to find out about "the implementation of character education in OSIS 1 Pontinak State High School". The method used is descriptive method with qualitative research. The data source of this research is the Student Council Supervisor, student council members and ordinary students who are not student council members. Data collection techniques used were observation techniques, interview techniques and documentation, while the data collection tools used were observation guides, interviews and documentation tools. There are 11 informants in this research. The results showed that the implementation of character education at OSIS Pontianak 1 High School was through student coaching activities that instill character values towards student council members who were realized by the student council through programmed activities. Character values that emerge are religious character values, responsibility, independence, tolerance, social care and environmental care. Evaluation of character education in OSIS Pontianak 1 High School is done by the OSIS Trustees by observing directly the behavior of students in a continuous manner in every planning and implementation activity and behavior of daily students in the school environment.